Effects of Microbial Inoculants on Fermentation Quality and Aerobic Stability of Paper Mulberry Silages Prepared with Molasses or Cellulase - Ying-Chao Zhang; Xue-Kai Wang; Yan-Li Lin; Yu-Long Zheng; Kui-Kui Ni; Fu-Yu Yang (Fermentation, 2022)
Paper mulberry (Broussonetia papyrifera L.) is an unconventional forage with high crude protein content and is widely used in China. In order to evaluate the pattern of fermentation quality and the aerobic stability when inoculated with lactic acid bacteria, laboratory-scale silage was prepared. The experimental groups included a control group (CK), a Lactobacillus plantarum ‘LC365283’ (selected from paper mulberry silage) treatment (L1), a commercial inoculant Lactobacillus plantarum treatment (GF), a commercial inoculant Lactobacillus buchneri treatment (FR), a 3% molasses treatment (MO), a 150 U/g cellulase treatment (CE), and their combinations (MO + L1, MO + GF, MO + FR, CE + L1, CE + GF, and CE + FR). The changes in bacterial community and composition of the fermentation products were evaluated after being ensiled for 30 days and unsealed for 1, 3, 5, and 7 days. Compared with the CK, MO and CE, the silages treated with L1, MO + L1, and CE + L1 showed higher lactic acid concentrations, lower pH values, and lower ammonia nitrogen concentrations (p < 0.05). During the first 3 days of aerobic exposure, the pH values and organic acid content changed slightly in all treatments. The present study suggests that addition of L1 was better than commercial inoculum, and the paper mulberry silages could be well preserved after being unsealed for 3 days.